Analysis of factors affecting the quality of life of people with type II Diabetes Mellitus - Afrianti, Novi; Rahmiati, Cut (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
Diabetes Mellitus is still a global health problem that has an impact on the welfare of individuals, families and communities and affects the quality of life of sufferers. The purpose of this study was to determine the factors that affect the quality of life of people with diabetes mellitus. This type of study used a cross sectional approach to 132 people with diabetes mellitus selected with a purposive sampling approach. Data collection by conducting interviews with type 2 DM patients and filling out the Diabetes Quality of Life Clinical Trial Quessionnaire (DQLCTQ) questionnaire The data analysis carried out was univariate and bivariate analysis using chi-square test and multivariate analysis using multiple logistic regression tests. The results showed that there was a relationship between knowledge (p = 0.000), dietary adherence (p = 0.044), medication adherence (p = 0.000), and family support (p = 0.000) with the quality of life of patients with type II diabetes. Of several factors, knowledge / education is the factor that has the strongest influence on the quality of life of people with type II DM.